INCOME ANALYSIS OF RUBBER FARMERS OF KUB MEMBERS IN KOTO TIBUN VILLAGE, THE KAMPAR DISTRICT, THE KAMPAR REGENCY - Shorea Khaswarina; Suardi Tarumun; Ilham Mudzakir (AGRIBUSINESS JOURNAL, 2022)
Research on rubber members of KUB was carried out in Koto Tibun Village, The Kampar District, and The Kampar Regency with the aim of analyzing net income and analyzing the efficiency level of rubber farming. This research was conducted using a survey method, the sampling was carried out by purposive sampling of 20 rubber farmers who were members of KUB using quantitative descriptive analysis of the income and the level of efficiency. The results showed that the average income of rubber farmers who were members of KUB was greater, amounting to IDR. 6,688,657.05 / ha/year and the RCR value of rubber farmers who were members of KUB was 1.33, meaning that every expense incurred by farmers was IDR. 1.00 will get a profit of IDR. 0.33. This means that the rubber farmer members of KUB are profitable and have been said to be efficient because the RCR value obtained is greater than one (RCR> 1).